Pigs in heaven : a novel - Kingsolver, Barbara (New York, NY : HarperCollins, 1993)
When a six-year-old child named Turtle is the sole witness to a freak accident at the Hoover Dam, she and her adoptive mother Taylor have a moment of celebrity that will change their lives forever. Turtle is claimed by Annawake Fourkiller, a Cherokee activist, to have been wrongly taken from the Cherokee nation. Fear of losing Turtle sends Taylor fleeing across the country with her mother Alice, pursued by Annawake. In the course of their journey, the three find love and wisdom in surprising places.
Keywords: Orphans -- Fiction; Cherokee Indians -- Oklahoma -- Fiction; Humorour stories; Domestic fiction; Love stories